In situ cross-linked carboxymethyl cellulose-polyethylene glycol binder for improving the long-term cycle life of silicon anodes in Li ion batteries - Lee, Dongsoo (2021)
To increase the energy density of Li-ion batteries (LIBs), silicon has been widely studied due to its relative abundance and high theoretical specific capacity (∼3572 mAh g–1). However, silicon experiences drastic volume changes up to 300% associated with Li. Here, we report an in situ cross-linked carboxymethyl cellulose-polyethylene glycol (CMC-PEG) binder and its application to the silicon anode to improve cycle life. Through in situ cross-linking during the electrode drying process, the cross-linked CMC-PEG binder is simply prepared without an additional process. In particular, the cross-linked CMC-PEG binder is effective in enhancing cohesion between active materials and adhesion between active materials and a current collector. The silicon anode with the cross-linked CMC-PEG binder shows stable cycling performance with a capacity of ∼2000 mAh g–1 up to 350 cycles at 0.5 C. In terms of simplicity, this binder has potential to be used for silicon anodes and other electrodes experiencing volume expansion during cycling.